Elaboration of the Environmental Stress Hypothesis–Results from a Population-Based 6-Year Follow-Up - Wagner, Matthias; Jekauc, Darko; Worth, Annette; Woll, Alexander (Frontiers in Psychology, 2016)
The aim of this paper was to contribute to the elaboration of the Environmental Stress Hypothesis framework by testing eight hypotheses addressing the direct impact of gross motor coordination problems in elementary-school on selected physical, behavioral and psychosocial outcomes in adolescence. Results are based on a longitudinal sample of 940 participants who were (i) recruited as part of a population-based representative survey on health, physical fitness and physical activity in childhood and adolescence, (ii) assessed twice within 6 years, between the ages of 6 and 10 years old as well as between the ages of 12 and 16 years old (Response Rate: 55.9%) and (iii) classified as having gross motor coordination problems (N = 115) or having no gross motor coordination problems (N = 825) at baseline. Motor tests from the Körperkoordinationstest, measures of weight and height, a validated physical activity questionnaire as well as the Strength and Difficulties Questionnaire were conducted. Data were analyzed by use of binary logistic regressions. Results indicated that elementary-school children with gross motor coordination problems show a higher risk of persistent gross motor coordination problems (OR = 7.99, p < .001), avoiding organized physical activities (OR = 1.53, p < .05), an elevated body mass (OR = 1.78, p < .05), bonding with sedentary peers (OR = 1.84, p < .01) as well as emotional (OR = 1.73, p < .05) and conduct (OR = 1.79, p < .05) problems in adolescence in comparison to elementary-school children without gross motor coordination problems. However, elementary-school children with gross motor coordination problems did not show a significantly higher risk of peer problems (OR = 1.35, p = .164) or diminished prosocial behavior (OR = 1.90, p = .168) in adolescence, respectively in comparison to elementary-school children without gross motor coordination problems. This study is the first to provide population-based longitudinal data ranging from childhood to adolescence in the context of the Environmental Stress Hypothesis which can be considered a substantial methodological progress. In summary, gross motor coordination problems represent a serious issue for a healthy transition from childhood to adolescence which substantiates respective early movement interventions.